Genetic Profile of Adenoid Cystic Carcinomas (ACC) with High-Grade Transformation versus Solid Type - Ana Flávia Costa; Albina Altemani; Hedy Vékony; Elisabeth Bloemena; Florentino Fresno; Carlos Suárez; José Luis Llorente; Mario Hermsen (Analytical Cellular Pathology)
Background: ACC can occasionally undergo dedifferentiation also referred to as high-grade transformation (ACC-HGT). However, ACC-HGT can also undergo transformation to adenocarcinomas which are not poorly differentiated. ACC-HGT is generally considered to be an aggressive variant of ACC, even more than solid ACC. This study was aimed to describe the genetic changes of ACC-HGT in relation to clinico-pathological features and to compare results to solid ACC.